Towards a New Platform Based on Web 2.0 Technologies Supporting Collaborative Clinical Reasoning Behavior Skills - Gherib, Teldja; Bouhadada, Tahar (International Journal of Emerging Technologies in Learning (iJET), 2021)
Clinical Reasoning (CR) is a complex skill that must be learned by students during their training. However, it is difficult to learn and it is not immediately apparent how training should be organized to develop and improve students' clinical reasoning behavior. The use of Web 2.0 technologies in e-learning and e-health provides opportunities to consider effective teaching and learning methods, with an emphasis on collaboration. The importance of collaboration in medical education and practice is growing, and by working together professionals can build a better future. When a shared information need becomes a collaborative site, it is called Collaborative Information Behavior (CIB). To date, there is no system that fully supports CIB in clinical reasoning learning. This paper focuses on studies conducted in the field of CIB. In addition, research related to the clinical reasoning learning in medical pedagogy is also considered. A model dedicated to the design of a collaborative clinical reasoning behavioral environment in synchronous mode is proposed. The proposed model was concretized by a collaborative environment supporting behavioral competencies in collaborative clinical reasoning based on Web 2.0 technologies (MEDcollab), which aims to make student learning visible and accessible to educators.